Perforeli Kanatlarda Şekil, Boyut Ve Eğim Açısının Isıl Performansa Etkisi - Jasim, Hisham H.; Söylemez, Mehmet Sait (Fırat University, 2018)
Bu çalışma elektronik parçaların soğutulmasında kullanılan perforeli kanatların ısıl performansını arttırmak için yapılmıştır. Dörtgen kesitli kanatlar için değişik tarzda eğimli bir perforeli kanat konusunda yeni ve orijinal sonuçlar elde edilmiştir. Mevcut modelin ısıl performans üzerindeki etkileri detaylı olarak araştırılmış ve sunulmuştur. Çalışmada teorik çözüm için Signum Fonksiyonu kullanılmıştır. Dejeneratf Hipergeometrik Denklemi ile birlikte Kummer’s Serisi kullanılarak genel çözüm elde edilmiştir. Mevcut sonuçlar ANSYS 16.0 ve sürekli rejim sonuçları ile mukayese edilerek doğrulanmıştır. Sonuçlar arasında bide üç ile altı mertebesinde farklılık görülmüştür. Ayrıca, sonuçlar ısı transfer alanının artmasıyla kanat sıcaklığının azaldığını göstermektedir. Perforasyon etkisi ile ısıl direncin azaldığı ve bu nedenle ısıl performansın yani kanat etkenlik değerinin arttığı gözlenmiştir

Many of the proposed methods introduced the perforated fin with the straight direction to improve the thermal performance of the heat sink. Present rectangular pin fin consists, innovative form of the perforation (with inclination angles). To investigate the thermal behavior of the present model, changes in each of the geometric consideration (shape, size and number of perforations) and inclination angles were considered. Signum function is used for the modeling the opposite and the mutable approach of the heat transfer area. The Degenerate Hypergeometric Equation (DHE) was used as a new derivative method to find the general solution, then solved by Kummer’s series. Two validation ways (previous work and Ansys 16.0-Steady State Thermal) are considered. The present mathematical model has big reliability according to the high agreement of the validation results about (0.31%- 0.60%). Also, the results show a decrease of the fin temperature as a result of the increase the heat transfer area. It was found, use of the perforated fin leads to decrease the thermal resistance and improve the thermal performance of the pin fin by enhancing the heat transfer and increase the effectiveness. Many of the proposed methods introduced the perforated fin with the straight direction to improve the thermal performance of the heat sink. Present rectangular pin fin consists, innovative form of the perforation (with inclination angles). To investigate the thermal behavior of the present model, changes in each of the geometric consideration (shape, size and number of perforations) and inclination angles were considered. Signum function is used for the modeling the opposite and the mutable approach of the heat transfer area. The Degenerate Hypergeometric Equation (DHE) was used as a new derivative method to find the general solution, then solved by Kummer’s series. Two validation ways (previous work and Ansys 16.0-Steady State Thermal) are considered. The present mathematical model has big reliability according to the high agreement of the validation results about (0.31%- 0.60%). Also, the results show a decrease of the fin temperature as a result of the increase the heat transfer area. It was found, use of the perforated fin leads to decrease the thermal resistance and improve the thermal performance of the pin fin by enhancing the heat transfer and increase the effectiveness.
The Effects of The Perforation Shapes, Sizes, Numbers and Inclination Angles on The Thermal Performance of A Perforated Pin Fin
Keywords: Engineering; Mühendislik